Continuous positive airway pressure delivery during less invasive surfactant administration: a physiologic study. (March 2018) - Jourdain, Gilles; Tersant, Marie; Dell'Orto, Valentina; Conti, Giorgio; De Luca, Daniele
Abstract Objective We sought to investigate the pressure delivery during less invasive surfactant administration, as we hypothesize that it might be reduced. Study design Physiologicin vitro study in a ventilation lab, using different pressure generators, levels, and leaks in a model of neonatal airways/lung mimicking mechanical characteristics of respiratory distress syndrome. Pressure was measured at the lung and verifiedin vivo measuring pharyngeal pressure in 19 neonates under same conditions. Data were analyzed using repeated measures-analysis of variance. Results Pressure deliveryin vitro is significantly and variably reduced during minimally invasive surfactant administration: pressure loss is ≈99% and ≈10–97%, during mouth opening and closure, respectively. Pressure loss seems independent from the type of CPAP and interface.In vivo measurements showed similar pressure drops. Conclusions Pressure transmission during minimally invasive surfactant administration is significantly reduced or totally absent. Pressure drop occurs despite the increased airway resistances and the airflow limitation due to the tracheal catheterization, but is independent from the type of pressure generator and interface.